Pelestarian Adat Hajat Solokan Sebagai Daya Tarik Wisata Budaya di Cikondang Desa Lamajang - Salma Raihan Imanda; Khoirul Fajri (Manajemen dan Pariwisata, 2022)
Lamajang village, has potential in tourism development both in terms of culture, agriculture, and unique tourist attractions. One of the important activities carried out in Lamajang Village is about cultural preservation, namely the Solokan Hajat Adat where this activity aims to express gratitude and gratitude. Researchers conducted research on these activities with the aim of knowing the process of implementing the Indigenous Hajat Solokan and efforts to preserve the Indigenous Hajat Solokan tradition which is used as a cultural tourist attraction. The research method used is a qualitative method with both primary and secondary data collection techniques, while both primary and secondary data collection is carried out by observation, interviews and documentation studies. Meanwhile, in analyzing data through the process of reduction, presentation and verification, primary data sources were obtained from the management of Lamajang Village, traditional leaders and community leaders and secondary data through the history book of the Cikondang Traditional House, journals regarding cultural preservation and sources relevant to the problems studied by the researchers. The results of the study concluded that the process ofimplementing the Solokan Hajat Adat had met the rules of a good event process, while in the preservation efforts for the protection element, the utilization of development had been fulfilled in the activity but there were still shortcomings, especially in the development element, it was not maximized because there was still a lack of involvement of the younger generation. With the existence of the local government as well as the community, the implementation of the Solokan Hajat Indigenous activities becomes mutual cooperation and goes well.